The Political Communication of Resolving Conflict on Public Policy : A Case Study of Mae Wong Dam Project - Brahmakappa, Akkaradecha (Arts of Management Journal, 2018)
The driven and ending of the Mae Wong dam project, which is a state-funded project or public policy, raises issues of conflict and mistrust at the level of the area. The interviews about of issues are addressed to people in the area. You will find that there is a facial expression, reaction, refusal and a question of who is coming from where, and the most obvious and most common is to not provide information because fear that his loved ones or family will suffer. The approach of the political communication to resolved the conflict, negotiation, inquiry, reconciliation, persuasion, supporting, competing or forcing and compelling, accommodating or smoothing, collaborating and participation. In order to maintain a good fellowship or fraternity, and develop and salvage as a brother with love, commitment, concern, concern. Help Felicity and good luck to happen, at the same time, it must avoid contempt. Discrimination and no exploitation in this area, to restore peace and peace back to the people in this watershed.